The Development THE DEVELOPMENT OF VIDEO SELF-ASSESSMENT FOR SOCIAL SKILLS IN THE TRADITIONAL GAME GOBAK SODOR IN PHYSICAL EDUCATION AT SENIOR HIGH SCHOOL 3 OF MALANG - Hasilul, Hasilul Mujahidil Ummi (JUARA : Jurnal Olahraga, 2025)
Social skills taught by teachers to students at school are very important to be applied as early learning before plunging into social life in the community and work later. This research aims to produce a new product in the form of an evidence-based social skills assessment instrument VSA (Video Self Assessment) using Borg and Gall's research and development (R&D) method which has been modified into 7 research steps. The data collection resulted from filling out the google form for social skills assessment instruments by students in the form of quantitative data then analyzed qualitatively by describing the data results and drawing conclusions. The results of this study indicate that the development of applied social skills assessment instruments can make it easier for students and teachers to assess social skills based on concrete evidence and are categorized as very appropriate to use